From decolonization to ethno-nationalism a study of Malaysia's school history syllabuses and textbooks 1905-2020 - Santhiram R. Raman (Strategic Information and Research Development Centre, 2021)
"Santhiram's critique of history education in Malaysia's school system, past and present is both valuable and timely. His study reaffirms that history's considerable value as an educative and academic undertaking is too often hijacked by political elites. This study is a salutary reminder why such tendencies should be challenged." -- S. Gopinathan